Persepsi Mahasiswa Terhadap Pembelajaran IPAS Dalam Kurikulum Merdeka - Irma Inesia Sri Utami; Rachmah Amalia; Shofia Hanna Nisa; Wafa Khilda Dalilah (FKIP, Universitas Palangka Raya, 2024)
The research aims to determine student perceptions of IPAS learning in the independent curriculum using qualitative research methods. Data was obtained through interviews with fourth semester PGSD students at Djuanda University using thematic analysis and data validity testing using source triangulation. The research results obtained four categories, which include: models, benefits, challenges and strategies in implementing IPAS learning. The research concluded that in the student perceptions, IPAS learning has various learning models, including Problem Based Learning, Discovery Learning, and Cooperative Learning which are useful in developing skills, forming character, and increasing students' scientific and social literacy. Even though there are challenges in implementing IPAS learning, teachers can develop learning strategies, such as conducting study visits, planning lessons, and forming Teacher Working Groups (KKG). This research contributes to supporting the implementation of IPAS learning in elementary schools